Fundamental study of hybrid graphene oxide and nanofibrillated cellulose for aircraft wings application - Kumaran, Kadirgama; Rahman, M. M.; Devarajan, Ramasamy; Mahendran, Samykano; Jose, Rajan
Strong synthetic fibers such as carbon fibers have an important role in a range of applications from aircraft to wind turbine blades. However, these fibers are expensive and demonstrate limited performance.The main objective is to develop well-aligned, strong microfibers prepared by hybridizing two-dimensional (2D) graphene oxide (GO) nanosheets and one-dimensional (1D) nanofibrillated cellulose (NFC) fibers and investigate the thermal physical properties. This hybrid material will have the potential to supersede carbon fibers due to their low cost and provide properties such as strength, elastic modulus and fatigue as carbon fibers. The heat carrier capability of hybrid 1D NFC and 2D GO with ethylene glycol and water mixture will be identified. Nanofluid will be prepared as two step method for thermophysical measurement. Thermal conductivity is measured by transient hot wire method using KD2-pro equipment and dynamic viscosity is measured using Brookfield DV-III. Both the experimental results and molecular dynamics simulations can reveal the synergistic effect between GO and NFC: the bonding between neighboring GO nanosheets is enhanced by NFC because the introduction of NFC provides the extra bonding options available between the nanosheets. Molecular dynamic simulation performs to study the bonding interaction and behaviour between particles and nanofibrillate. It is expected the hybrid material can perform as carbon fiber in term of mechanical properties.The significant output will be hybrid 1D NFC and 2D GO which can be able to enhance mechanical property for high strength application and enhance thermophysical property for heat transport application. Template-assisted electrochemical deposition approach successfully synthesized high purity graphene (97.97% based on EDX analysis), 2. Qualitative analysis from FESEM images showed that all the surface texture of graphene found to be rough and flaky with rough surface texture when the deposition temperature increase. 3. XRD analysis suggests that all the grown graphene is polycrystalline in nature and the obtained XRD spectrum does not show any change in the crystal orientation when different synthesis condition was applied. However, increase in crystal size was noticed when deposition temperature increased, and it is also noted that the average of crystal size increase in small amount when the stabilizer concentration reduced. From MD simulation, the estimated elastic modulus for graphene is between 140.02 to 142.5 GPa, the yielding stress between 16.465 to 16.732 GPa and the yielding strain between 0.1181 to 0.1209. Due to the increasing demand in industrial application, nanofluids have attracted the considerable attention of researchers in recent decades. The addition of nanocellulose (CNC) with water (W) and ethylene glycol (EG) to a coolant for a radiator application exhibits beneficial properties to improve the efficiency of the radiator . The focus of the present work was to investigate the performance of mono or hybrid metal oxide such as Al2O3 and TiO2 with or without plant base-extracted CNC with varying concentrations as a better heat transfer nanofluid in comparison to distilled water as a radiator coolant. The CNC is dispersed in the base fluid of EG and W with a 60:40 ratio. The highest absorption peak was noticed at 0.9% volume concentration of TiO2, Al2O3, CNC, Al2O3/TiO2, and Al2O3/CNC nanofluids which indicates a better stability of the nanofluids’ suspension. Better thermal conductivity improvement was observed for the Al2O3 nanofluids in all mono nanofluids followed by the CNC and TiO2 nanofluids, respectively. The thermal conductivity of the Al2O3/CNC hybrid nanofluids with 0.9% volume concentration was found to be superior than that of the Al2O3/TiO2 hybrid nanofluids. Al2O3/CNC hybrid nanofluid dominates over other mono and hybrid nanofluids in terms of viscosity at all volume concentrations. CNC nanofluids (all volume concentrations) exhibited the highest specific heat capacity than other mono nanofluids. Additionally, in both hybrid nanofluids, Al2O3/CNC showed the lowest specific heat capacity. The optimized volume concentration from the statistical analytical tool was found to be 0.5%. The experimental results show that the heat transfer coefficient, convective heat transfer, Reynolds number and the Nusselt number have a proportional relationship with the volumetric flow rate. Hybrid nanofluids exhibit better thermal conductivity than mono nanofluids. For instance, a better thermal conductivity improvement was shown by the mono Al2O3 nanofluids than the CNC and TiO2 nanofluids. On the other hand, superior thermal conductivity was observed for the Al2O3/CNC hybrid nanofluids compared to the other mono and hybrid ones (Al2O3/TiO2).